Reverse iontophoretic extraction of metabolites from living plants and their identification by ion-chromatography coupled to high resolution mass spectrometry - González Sánchez, M; McCullagh, J; Guy, R; Compton, R (Wiley, 2016)
Introduction - The identification and characterisation of cellular metabolites has now become an important strategy to obtain insight into functional plant biology. However, the extraction of metabolites for identification and analysis is challenging and, at the present time, usually requires destruction of the plant. Objective – To detect different plant metabolites in living plants with no pre-treatment using the combination of iontophoresis and ion-chromatography with mass spectrometry detection. Methodology – In this work, the simple and non-destructive method of reverse iontophoresis has been used to extract in situ multiple plant metabolites from intact Ocimum basilicum leaves. Subsequently, the analysis of these metabolites has been performed with ion chromatography coupled directly to high resolution mass spectrometric detection (IC-MS). Results – The application of reverse iontophoresis to living plant samples has avoided the need for complex pre-treatments. With this approach, no less than 24 compounds, including organic acids and sugars as well as ATP were successfully detected. Conclusion- The research demonstrates that it is feasible to monitor, therefore, a number of important plant metabolites using a simple, relatively fast and non-destructive approach.